One-step synthesis of high-quality homogenous Te/Se alloy nanorods with various morphologies1. Issue 17 (7th May 2015) - Fu, Shilin; Cai, Kai; Wu, Long; Han, Heyou
<x xml:space="preserve">Abstract</x> A convenient method was developed for controllable synthesis of homogeneous trigonal Te/Se alloy nanorods (t-Te/Se ANRs) with diverse morphologies, aspect ratios and compositions at room temperature in aqueous solution.